Diagnostic approach to brachycephalic syndrome in dogs: literature review (Research, Society and Development, 2021)
The early recognition of brachycephalic syndrome is extremely important for a better post-surgical prognosis, and the association of various research methods is essential for its determination. The diagnosis of the syndrome is based on an accurate anamnesis together with the observation of characteristic clinical signs and complementary exams, such as hematological exams and imaging exams. Among the imaging tests, radiography, rhinoscopy and computed tomography are commonly used, which help both in the diagnosis of the syndrome and in surgical planning, when indicated. Given the importance of accurate diagnosis of this disease in affected dogs, the current study aimed to carry out an updated literature review addressing the different diagnostic methods for BS. It can then be concluded that the correct identification of brachycephalic syndrome by veterinarians through different diagnostic tools is extremely important to establish an early treatment, minimizing the acute risk of death and increasing the quality of life and welfare of affected animals.